Evaluating the Productivity of the National General Insurance Company by using the Production Function - Douglas Cup For the period from 2009 – 2019 - L. , Mohammed I.T. Alan; L. , Firas A. Mohammed. AL kurtany; L. , Amer Rashid Aanid AL msoodi (International Journal of Psychosocial Rehabilitation, 2020)
The aim of the study is to estimate the productivity of the National Insurance Company using the Douglas Cup production function and then measure the extent of the contribution of each of the independent variables and its effect on the dependent variable and thus knowledge of the elements that have a significant or nonsignificant effect on the dependent variable. Hence, the importance of research in estimating the production function of Douglas Cup for the General National Insurance Company for the years (2009-2019) in order to demonstrate the extent of the contribution of each of the independent variables represented by (investment, number of employees, value of production requirements) on the adopted variable represented by (production value) By using the letter regression method in the estimation, the most prominent conclusions and recommendations were reached, which is that the production function when using the adopted variable (production value) and the independent variables (number of workers and production requirements) represents the best production function expressing the activity of the General National Insurance Company. And represented by wages and salaries paid through cash wages, in-kind, incentives, and cash and in-kind rewards as well.